Oral health education strategies for patients living with cardiovascular disease within hospital settings: a scoping review - Church, L. A.; Robins, L.; Xu, F.; Qin, L.; Tran, A.; Wallace, J. P.; King, S. (Frontiers in Public Health, 2024)
Objective To identify and describe the impact of current oral health education programmes provided to patients in cardiology hospital wards and outpatient clinics. Methods This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Scoping Reviews statement. Searches were conducted using electronic databases: Cochrane, Medline, and Scopus, as well as grey literature searching. Results Three eligible studies were identified. All included studies reported generalised poor oral health in their participants at baseline, with significant improvement at follow-up. They all reported significant reductions in plaque deposits and gingival bleeding. One study reported significantly less bacteria on participant tongues, as well as fewer days with post-operative atrial fibrillation in the intervention group. Furthermore, in this study, one patient in the intervention group developed pneumonia, whilst four patients in the control group did. Conclusion Oral health education for patients with cardiovascular disease is limited and many have poor oral health. Educational programmes to improve oral health behaviours in patients with cardiovascular disease can improve both oral and general health outcomes. Implications for public health Oral disease is a modifiable risk factor for cardiovascular disease. Integrating oral health education into cardiology hospital settings is a simple strategy to improve access to oral health information and improve both oral and cardiovascular outcomes.